Persembahan Animasi: Perspektif Penting Untuk Ict Multimedia - Fong , Soon Fook (Penerbit Universiti Sains Malaysia, 2000)
This study examined the effects of animated graphics in a multimedia computerbased learning presentation on the procedural knowledge of a biology topic entitled Meiosis. A twohour lesson was developed in three different modes, text with static graphics (TGS), text with animated graphics (TGA) and text with transitional-animated graphics (TGAB).